Brief history of curriculum and teacher training in Colombia - Gerardo Bazante Caldas (Práxis Pedagógica, 2006)
The following text, which is a short review of the history of education in Colombia, emphasizes the relationship that exists between curriculum and teacher training. It also presents curriculum in its precarious conception which binds it to the syllabus and to some not-well-defined purposes that are due to the evolution of a history full of turbulence in which the war has been the major figure and the governors have resorted to occasional resources more related to improvisation rather than economical and political development of Colombia. The rapid progression of globalization has led to preserve the same course of improvisations which change in accordance with the administrator of the moment that reaches the Government and whose shape is given in accordance with the foreign interests that hinder the possibility of a more suitable development for colombian interests. The last part of the text calls for the teachers to construct their own history and recover the role they have in the society and culture.